Stres Kerja dengan Perilaku Caring Petugas Kesehatan dalam Penanganan Pasien pada Masa Pandemi Covid-19 - Lisnawati Yupartini; Epi Rustiawati; Tuti Sulastri (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the relationship between work stress of health workers and caring behavior at the Serang City Health Center. This type of research is an analytic survey with a cross-sectional design. The results showed that 43.2% of health workers with moderate stress and 29.1% of health workers lacked caring. The results of the bivariate analysis showed that the value (p = 0.00). In conclusion, there is a relationship between the work stress of health workers and caring behavior at the Puskesmas in Serang City in 2020 Keywords: Caring, Covid-19 Pandemic, Work Stress, Health Workers